2022
DOI: 10.3390/en15228694
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mixing Uniformity of Hydrogen Injection inNatural Gas Pipeline Based on a Deep Learning Model

Abstract: It is economical and efficient to use existing natural gas pipelines to transport hydrogen. The fast and accurate prediction of mixing uniformity of hydrogen injection in natural gas pipelines is important for the safety of pipeline transportation and downstream end users. In this study, the computational fluid dynamics (CFD) method was used to investigate the hydrogen injection process in a T-junction natural gas pipeline. The coefficient of variation (COV) of a hydrogen concentration on a pipeline cross sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The velocity values and HMRs of the gases at different positions in the pipeline are counted through 33 monitoring points. The velocity COV 32 is the ratio of the standard deviation to the mean value, which reflects the flow distribution of the mixed gases in the pipeline, and the formula is…”
Section: Mathematical Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…The velocity values and HMRs of the gases at different positions in the pipeline are counted through 33 monitoring points. The velocity COV 32 is the ratio of the standard deviation to the mean value, which reflects the flow distribution of the mixed gases in the pipeline, and the formula is…”
Section: Mathematical Equationmentioning
confidence: 99%
“…The velocity values and HMRs of the gases at different positions in the pipeline are counted through 33 monitoring points. The velocity COV 32 is the ratio of the standard deviation to the mean value, which reflects the flow distribution of the mixed gases in the pipeline, and the formula is COV=sv¯=1v¯1n1i=1n(viv¯)2, $COV=\frac{s}{\bar{v}}=\frac{1}{\bar{v}}\sqrt{\frac{1}{n-1}\sum _{i=1}^{n}{({v}_{i}-\bar{v})}^{2}},$where n is the number of monitoring points selected in the cross‐section, v i is the velocity of the monitoring point, m/s; truev¯ $\bar{v}$ is the average value of the velocity over the monitored section, m/s.…”
Section: Computational Modelmentioning
confidence: 99%
“…The first method involves branch pipe mixing, where initially the gas stratification occurs due to density differences, followed by complete mixing during the transportation process. 15,16 The second method involves preblending hydrogen gas and natural gas in a mixing equipment before pipeline transportation, ensuring a fully homogeneous gas mixture. 17,18 Currently, to mitigate the occurrence of HENG stratification, the industry typically resorts to the second approach: Completely mixing was conducted within hydrogen blending stations prior to transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, two primary methods are commonly used to mix hydrogen gas into natural gas pipelines. The first method involves branch pipe mixing, where initially the gas stratification occurs due to density differences, followed by complete mixing during the transportation process. , The second method involves preblending hydrogen gas and natural gas in a mixing equipment before pipeline transportation, ensuring a fully homogeneous gas mixture. , Currently, to mitigate the occurrence of HENG stratification, the industry typically resorts to the second approach: Completely mixing was conducted within hydrogen blending stations prior to transportation. However, the issue of whether such well-mixed HENG will restratify under conditions of pipeline shutdown or during vertical riser transit constitutes a focal point of research within the academic community.…”
Section: Introductionmentioning
confidence: 99%
“…Eames [11] investigated a transmission pressure pipe equipped with a vertical Tee junction and showed that the injection rate, side pipe diameter, and injection location significantly affect the mixing process mainly due to a density contrast of eight times between hydrogen and methane. A deep neural network (DNN) model was developed in [12] to predict the mixing quality of hydrogen and natural gas in low-pressure bottom-sided Tee junctions. In another work, it was suggested that adding a static mixer, such as a helical static mixer, can improve the stratification of gases, resulting in a more uniform mixture [13].…”
Section: Introductionmentioning
confidence: 99%